The Crucial Role of Sportsmanship in Fostering Positive Values and Building an Inclusive Sports Community - Idris, Fahmi; Lubay, Lukmanul Haqim; Anira, Anira; Putri, Wulandari (Media Ilmu Keolahragaan Indonesia, 2024)
This article explores the vital role of sportsmanship within the context of sports, focusing on the development of positive values among adolescents and adults. Sportsmanship is not merely about physical competition but also encompasses attitudes and behaviors that reflect fair play. Among adolescents, participation in sports enhances not only physical performance but also fosters character development, responsibility, and the ability to cope with defeat in a resilient manner. Moreover, sportsmanship serves as a foundation for mutual respect and cooperation in social interactions. At the adult level, sportsmanship is essential for creating a positive environment in sports practice. Mutual respect, humility, and a willingness to collaborate form the basis for building an inclusive and supportive sports community. In the adult sphere, sportsmanship also contributes to reducing tensions and conflicts, thus positively influencing the workplace and daily life. Therefore, this article highlights the importance of sportsmanship as a valuable asset for character development and the cultivation of a society grounded in positive values.